(3eff GdYdi GdcHjQ HahGFO CMeO GdUZjQs - (3eMeO Hf CMeO GdUZjQ GdeSdej GdJjTjJjs ((3YHO GdQMef Hf eMeO LO Hf GYeQ s)
(3ChdgG (B:s
(3CeG HYO ajbhd eMeO Hf CMeO GdUZjQ deG cGf GdYdeG GdfGaY NjQ eG Cfab ajg GdYGbd YeQg bUOJ eSJYjfkG HGddg LeY eSGFd ef egeGJ GdYde YOjOI eeG GfJbGg hGdOi s
(3BNQgG (B:s
(3hCaVd GdYdhe Ydhe GdTQjYI , hCaVd Pdc ef hab Cf jMhP bQGAI GdbQBf Ke jMaX MOjK GdfHi hjYQa UMjMg ef SbjeI , Ke jbQC CUhd Gdabg hef bUQ Yf Pdc adjbQC GdeSGFd Ydi ePgH eGdc s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMI s
(3HYV YHGQGJgG HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3Gdabg GdESdGejs